Determinant factors of infant mortality in Bima District in 2012 - Rini Hendari; I Ketut Tangking Widarsa; Dewa Nyoman Wirawan (Public Health and Preventive Medicine Archive, 2013)
The infant mortality is the death of a child before the age of one year, can be caused by endogenous and exogenous factors. The infant mortality rates influenced by family income, maternal age, birth spacing, the frequency of the ANC visits, the place of delivery, birth weight, breastfeeding, immunisation, maternal knowledge about infant care, clean water sources sanitationary and education related to infant mortality. The purpose of this research was to identify the determinant factors of infant mortality in Bima regency. The type of research is observational analytic, with a case-control study design. The cases were infant who died in January to December 2012, while the control were infant who still alive on the same period. Cases and controls were selected from the community of Bima District. They were selected by using stratified proportional sampling technique and in total they were 153 respondents with a ratio of 1 to 2. Data was collected through interviews and midwives registers documentation. Data were analysed using chi square test and logistic regression. The result showed that the birth weight <2500 gr OR=6.69 (95%CI: 2.11-21.16), birth spacing <24 months OR=6.69 (95%CI: 2.11-21.16), maternal age <20 or >35 years OR=6.63 (95%CI: 1.84-23.90), not exclusively breastfeeding OR=6.23 (95%CI: 2.10-18.46), education related to infant mortality OR=6.02 (95%CI: 2.17-16.65) and clean water sources sanitationary OR=3.72 (95%CI: 1.35-10.25). It can be concluded that birth weight <2500 gr, spacing births <24 months, maternal age <20 or >35 years, not exclusively breastfeeding, education related to infant mortality, clean water sources sanitationary were determinants of infant mortality with the overall contribution of 61.1%. Improving education and promotion related to nutritional requirement for pregnant women, delay in age of marriage, pregnancy planning and exclusive breastfeeding in Bima District are highly essential.